Introduction to data visualization with R and ggplot2 - Chang, Winston (O'Reilly Media, Inc., 2014)
"Visualization is an essential part of a data analyst's toolkit. When you're in the exploratory phase of data analysis, visualizations can help you understand data and find patterns in it. Later, when you want to present the data to others, visualizations are essential for efficiently communicating your findings. In this webcast presented by Winston Chang, author of R graphics Cookbook, you'll learn the basics of how to create data graphics using R and the popular ggplot2 package."--Resource description page.
Title from resource description page (Safari, viewed August 26, 2014)
Keywords: Information visualization; Computer graphics -- Design; Computer graphics; Design; Visualisation de l'information; Electronic videos